2022
DOI: 10.1021/acs.chemmater.2c00262
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Suppressed Porous Processable Hexa-Zirconium/Polymer Composites for Detoxification of a Nerve Agent Simulant

Abstract: We describe a composite in which reactive hexanuclear zirconium (Zr 6 ) clusters were encapsulated in the micropores of processable polymers of intrinsic microporosity (PIMs). By varying the amount of Zr 6 clusters in PIMs, it was possible to tune the loading of Zr 6 in two polymer matrices: the pristine PIM-1 and the amidoxime-functionalized PIM (PIM-1-AO). Aggregation of Zr 6 clusters was suppressed in both Zr 6 @PIM composites to achieve improved hydrolysis performance of a nerve agent simulant, dimethyl 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…UiO-66-NH 2 MOF materials considered as gold standard materials have t 1/2 ranging from 0.5 to 45 min in buffers having pH = 9−10. 14,27 A recent study by Su et al demonstrated DMNP degradation in borate buffer (pH = 8.04) with their best achieved t 1/2 ∼1 h. 37 Overall, the rates of reactivity obtained in the presented research are comparable to the aforementioned results and are potential candidates for inexpensive, scalable polymeric alternatives broadening the scope of applicable Chem-Bio protective materials. The halflives of DMNP, when exposed to all P4VP-Ox substrates, is further summarized in Figure 6a.…”
Section: ■ Results and Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…UiO-66-NH 2 MOF materials considered as gold standard materials have t 1/2 ranging from 0.5 to 45 min in buffers having pH = 9−10. 14,27 A recent study by Su et al demonstrated DMNP degradation in borate buffer (pH = 8.04) with their best achieved t 1/2 ∼1 h. 37 Overall, the rates of reactivity obtained in the presented research are comparable to the aforementioned results and are potential candidates for inexpensive, scalable polymeric alternatives broadening the scope of applicable Chem-Bio protective materials. The halflives of DMNP, when exposed to all P4VP-Ox substrates, is further summarized in Figure 6a.…”
Section: ■ Results and Discussionsupporting
confidence: 72%
“…Overall, nanofiber materials fabricated upon electrospinning P4VP-OOx 20% provided the most rapid degradation kinetics with t 1/2 = 14.4 and 26.6 min using 53 and 27 mg of the substrate, respectively (bold values in Table ). UiO-66-NH 2 MOF materials considered as gold standard materials have t 1/2 ranging from 0.5 to 45 min in buffers having pH = 9–10. , A recent study by Su et al demonstrated DMNP degradation in borate buffer (pH = 8.04) with their best achieved t 1/2 ∼1 h . Overall, the rates of reactivity obtained in the presented research are comparable to the aforementioned results and are potential candidates for inexpensive, scalable polymeric alternatives broadening the scope of applicable Chem-Bio protective materials.…”
Section: Resultsmentioning
confidence: 99%
“…The 30 wt % Ce­(OH) 4 -coated Matrimid (Ce­(OH) 4 @Matrimid-Coat) and 30 wt % Zr­(OH) 4 -coated Matrimid (Zr­(OH) 4 @Matrimid-Coat) composites were fabricated by applying a solution containing NMP, chloroform, and ethanol in the ratio of 8:1:1, respectively, on the bare Matrimid to achieve a gel-like surface, after which brush was applied to create voids within the gel to improve the adhesion between the Matrimid substrate and the metal hydroxide particles. Following the formation of the gel-like composite, Ce­(OH) 4 or Zr­(OH) 4 particles were sprayed onto the surface of the polymer using the powder-spray gun and then dried at 40 °C for 48 h. In contrast, 30 wt % Ce­(OH) 4 -coated PIM-1 (Ce­(OH) 4 @PIM-1-Coat) and 30 wt % Zr­(OH) 4 -coated PIM-1 (Zr­(OH) 4 @PIM-1-Coat) composites were fabricated using the non-textured spray-coating technique (see Figure a) due to the low yield strength and toughness of PIM-1 . A mixture of DMF, ethanol, and chloroform (1:1:8) was applied to the surface of the bare PIM-1 polymer, after which 0.3 g of Ce­(OH) 4 or Zr­(OH) 4 was sprayed on the PIM-1’s wet surface and allowed to dry in a vacuum oven at 40 °C for 48 h.…”
Section: Methodsmentioning
confidence: 99%
“…Organophosphorus nerve agents, including sarin, soman, and VX, are a class of the most toxic chemical warfare agents (CWAs) that can easily penetrate human mucosa to disrupt the central nervous system, resulting in constant muscle contraction and even death. , The use of organophosphorus nerve agents in terrorist attacks and assassination poses severe threats to human beings . In this context, there is a growing interest in developing effective materials/catalysts for degrading nerve agent stockpiles and for employment in personal protective equipment. …”
Section: Introductionmentioning
confidence: 99%